Graph theory and its applications - Conference on Graph Theory and its Applications (2001 : Anna University); Balakrishnan, R.; Sethuraman, G.; Wilson, Robin J. (New Delhi : Narosa Publishing House, 2004)
Contributed papers presented at the Conference on Graph Theory and its Applications, held on March 14-16, 2001, at Anna University, Chennai
Includes bibliographical references
Keywords: Graph theory -- Congresses